Adnexotropic Variants of the Interface Dermatitides: A Review - Carla Stephan; Ossama Abbas; Jag Bhawan (MDPI AG, 2021)
The interface dermatitides encompass a vast array of cutaneous entities which, at times, may present with particular clinical variants with adnexal predilection. Similarly, hair follicle and eccrine gland involvement of some of these entities has been observed on histopathology. This review aims to describe the various adnexotropic presentations of the interface dermatitides. Recognizing that the adnexa can be a frequent site of involvement of these conditions may aid dermatopathologists in making the correct diagnosis and avoid misinterpreting adnexotropism for other conditions such as the great imitator, mycosis fungoides.